Preparation of Carrageenan/Chitosan/Curcumin Hydrogel Films: Physicochemical Characterization and In Vitro Evaluation as a Promising Diabetic Wound Dressing - Sry Agustina; Saidun Fiddaroini; Ahmad Luthfi Fahmi; Ruslan; Elvina Dhiaul Iftitah; Moh. Farid Rahman; Akhmad Sabarudin (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Wound dressings with their physical characteristics that can maintain moisture and their active content which possesses antibacterial and antioxidant properties, represent a crucial solution in addressing the delayed healing of diabetic wounds. For this purpose, in this work we prepared hydrogel films made from a combination of carrageenan, chitosan, and curcumin, and subsequently evaluated their performance for potential application as the diabetic wound dressings. There were three hydrogel film formulations fabricated using 0.5% chitosan, 0.05% curcumin, and carrageenan at varying concentrations of 1%, 1.5%, and 2%, which were subsequently designated as A1, A2, and A3, respectively. These films were examined for physical parameters, chemical profiles, antibacterial activity against Staphylococcus aureus and Escherichia coli, and antioxidant activity (DPPH assay). The A2 film formulation demonstrated optimal characteristics, as evidenced by a high swelling capacity of 1439.67 ± 20.36%, an appropriate moisture content of 20.63 ± 0.49%, a film pH of 6.23 ± 0.31%, favorable degradation behavior of 93.27 ± 1.36%, and a film thickness of 0.20 ± 0.001 mm. This formulation also demonstrated superior antibacterial activity against Staphylococcus aureus and Escherichia coli, accompanied by strong antioxidant activity (IC50 = 74.52 ppm). Such results indicate that the carrageenan/chitosan/curcumin hydrogel film, particularly formulation A2, is a promising smart hydrogel dressing candidate for diabetic wound applications.